The Impact of Library Instruction on Medical Student Information Seeking Behavior - Barr, Angela (VCU Scholars Compass, 2022)
Background To describe initial efforts to impact the information seeking behaviors of medical students during Grand Rounds exercises completed in their first and second years of pre-clinical education. Description Librarians received student responses to an information literacy question that is embedded in the Grand Rounds activity and analyze the data as follows. Sources were tallied and grouped according to resource type. Next, librarians attempted to assess the quality of certain sources. Third, search terms provided by students were aggregated and analyzed to determine frequency of use. Finally, a DML librarian-educator presented the compiled data to the entire class, making suggestions for improving searching, and clarifying expectations for how to improve their resource choices for their M2 Grand Rounds session. This process was repeated in either the fall or spring of the M2 year with a different Grand Rounds scenario. Conclusions In the real-world application of back-to-back GUSoM Grand Rounds exercises, librarian-led instruction on clinical-specific resources appears to be correlated with an improvement in medical students’ searching behavior between their M1 and M2 years. This trend supports the argument that introducing students early to librarian-led education on clinical-specific resources, and providing feedback on their searches, improves students’ information seeking behavior.